PRTAD: A database for protein residue torsion angle distributions. (11th November 2009) - Sun, Xiaoyong; Wu, Di; Jernigan, Robert; Wu, Zhijun
PRTAD is a dedicated database and structural bioinformatics system for protein analysis and modelling. The database is developed to host and analyse the statistical data for protein residue level 'virtual' bond and torsion angles obtained from their distributions in databases of known protein structures such as in the PDB Data Bank. PRTAD is capable of generating, caching, and displaying the statistical distributions of the angles of various types. The collected information can be used to extract geometric restraints or define statistical potentials for protein structure determination. PRTAD is supported with a friendly designed web interface so that users can easily specify the angle types, and retrieve, visualise, or download the distributions of the angles as they desire.